Emerging Markets: Evaluating Graham's Stock Selection Criteria on Portfolio Return in Saudi Arabia Stock Market - Zakaria, Nadisah; Hashim, Fariza (International Journal of Economics and Financial Issues, 2017)
Graham's stock selection criteria enable investors to be more cautious in selecting their portfolios in order to generate abnormal return. Graham's model was widely examined in various developed market where the stock markets and companies are more mature and economy of the countries are more stable. However, the selection criteria model was not commonly examined in emerging countries despite of their rapid economic growth and diversified sectors in the stocks trading. Hence, this study attempts to investigate the relevance of Graham's stock selection criteria on the portfolio returns of the Saudi Arabia stock market. Saudi Arabia represents the fastest growing market in the Middle East primarily AGCC region thus testing the market is justified. The study found that despite of being young and immature stock market, Saudi stock market was able to offer abnormal return to the investors and Graham's model of stock selection is indeed valuable to investors. Keywords: net current asset value, Benjamin Graham, value investing JEL Classification: G14